Bendamustine Associated with Irreversible Ascending Paralysis. (27th February 2013) - Alhafez, Ashraf; Aljitawi, Omar S.; Lin, Tara L.; Ganguly, Siddhartha; Abhyankar, Sunil; McGuirk, Joseph P.
Abstract : Bendamustine is an alkylating agent currently used in the treatment of lymphoproliferative disorders. Many adverse effects, including a rare case of reversible neurotoxicity, have been reported in association with bendamustine. Herein, we report the first case of irreversible ascending paralysis related to bendamustine.